Highly Emissive Self‐Trapped Excitons in Fully Inorganic Zero‐Dimensional Tin Halides. Issue 35 (30th July 2018) - Benin, Bogdan M.; Dirin, Dmitry N.; Morad, Viktoriia; Wörle, Michael; Yakunin, Sergii; Rainò, Gabriele; Nazarenko, Olga; Fischer, Markus; Infante, Ivan; Kovalenko, Maksym V.
Abstract: The spatial localization of charge carriers to promote the formation of bound excitons and concomitantly enhance radiative recombination has long been a goal for luminescent semiconductors. Zero‐dimensional materials structurally impose carrier localization and result in the formation of localized Frenkel excitons. Now the fully inorganic, perovskite‐derived zero‐dimensional Sn II material Cs4 SnBr6 is presented that exhibits room‐temperature broad‐band photoluminescence centered at 540 nm with a quantum yield (QY) of 15±5 %. A series of analogous compositions following the general formula Cs4− x A x Sn(Br1− y I y )6 (A=Rb, K; x ≤1, y ≤1) can be prepared. The emission of these materials ranges from 500 nm to 620 nm with the possibility to compositionally tune the Stokes shift and the self‐trapped exciton emission bands. Abstract : Fully inorganic, perovskite‐derived zero‐dimensional Cs4 SnBr6 exhibits room‐temperature broad‐band photoluminescence from self‐trapped excitons, centered at 540 nm with a quantum yield of 15±5 % (298 K; near 100 % at 200 K), and a large Stokes shift of ca.1.2 eV. A compositional series, Cs4− x A x Sn(Br1− y I y )6 (A=Rb, K; x ≤1, y ≤1), was obtained wherein the emission peak ranges from 500 nm to 620 nm.